Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2006
DOI: 10.1088/0031-9155/51/24/009
|View full text |Cite
|
Sign up to set email alerts
|

Charge collection efficiency in ionization chambers exposed to electron beams with high dose per pulse

Abstract: The correction for charge recombination was determined for different plane-parallel ionization chambers exposed to clinical electron beams with low and high dose per pulse, respectively. The electron energy was nearly the same (about 7 and 9 MeV) for any of the beams used. Boag's two-voltage analysis (TVA) was used to determine the correction for ion losses, k(s), relevant to each chamber considered. The presence of free electrons in the air of the chamber cavity was accounted for in determining k(s) by TVA. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
142
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(161 citation statements)
references
References 14 publications
13
142
0
Order By: Relevance
“…In clinical practice, this condition is usually satisfied. However, the two‐voltage method has been shown to be notably inaccurate for both low electric field strength (6) and very large doses per pulse 14 , 15 . Piermattei et al, (14) for example, showed substantial error in the recombination correction estimated by the two‐voltage technique for a high dose‐per‐pulse intraoperative electron therapy accelerator.…”
Section: Introductionmentioning
confidence: 99%
“…In clinical practice, this condition is usually satisfied. However, the two‐voltage method has been shown to be notably inaccurate for both low electric field strength (6) and very large doses per pulse 14 , 15 . Piermattei et al, (14) for example, showed substantial error in the recombination correction estimated by the two‐voltage technique for a high dose‐per‐pulse intraoperative electron therapy accelerator.…”
Section: Introductionmentioning
confidence: 99%
“…In order to determine the absorbed dose, the chamber signal is corrected by using many factors as indicated in IAEA 398 protocol [41]. In particular, the ion recombination correction factor k s was calculated following the method proposed in Laitano et al [6] for each investigated fields in order to reduce the inaccuracy in the measurements due to the high dose per pulse with respect to the conventional electron beam [8,42,6]. The values used in this work are reported in Table 1.…”
Section: Ionization Chamber Measurementsmentioning
confidence: 99%
“…The main difference is related to the high dose per pulse of IORT dedicated LINACs that does not allow the direct use of ionization chamber as recommended in the protocol IAEA 398 for the absolute dose determination because of ion recombination effects [6]. Indeed, because of the high density of electric charge produced in the ionization chamber's volume per radiation pulse, the correction factor k s for ion recombination is overestimated if the correction methods recommended by the current international dosimetry protocols are used [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…From the calculated values of ! and measured values of in air, fitting expressions have been deduced (Hochhauser et al, 1994;Laitano et al, 2006). Fig.…”
Section: Effects Of Space Charge and Free Electronsmentioning
confidence: 99%